APLIKASI SISTEM TAMU PONDOK PESANTREN SUMBER BAROKAH KARAWANG BERBASIS WEB - Kholifin Hilman Suharno; Carudin Carudin; Kamal Prihandani (Jurnal Ilmiah Wahana Pendidikan, 2023)
Abstract. Guest visit is a common thing happen in many places, both privat also public places, moreover for an instantion, like governments and public instantion. Guest is a personal or a group who come to visit to a place or banquet. In proses of accepting guest, sometime found problems in data management and serving guest it self. In general, this happen because of the data management is still in konventional and unpreparedness of the instantion in serving guest because of unavailable concrete data. Because of that, for solving the problem, need a guest system application that can save the data structurally, latestly and informatively, interactively, dynamically, achievely well, also easy to use for every user as they need it, where ever it used. Application is an implementation of system design to process data by using rules or provisions of certain programming languages. The guest system is a sequence of stages in managing guest data. In this research, applications are designed to use web-based applications using javascript programming language with helping of the NativeScript framework. The guest system application development uses the Software Development Life Cycle (SDLC) method which has the following stages: needs analysis, design, coding, testing, and support